In Silico Perturbome Analysis Reveals Conserved Genes and Drug–Target Interactions in Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus in the Response to Stress - Molina Mora, José Arturo (2026)
Background: Bacterial adaptation to environmental and chemical stress involves coordinated, system-level responses collectively described as perturbome. Understanding conserved elements within core perturbomes may reveal strategic vulnerabilities for antimicrobial development. Methods: In this study, we implemented an integrative framework combining functional and comparative genomics, drug-target interactions and molecular docking to prioritize conserved stress-response targets in Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Results: A total of 147 genes from previously defined core perturbomes were analyzed through interactome reconstruction and functional enrichment. Interactome and functional analyses revealed significant connectivity and functional clustering, primarily associated with molecule biosynthesis, translation, transcriptional regulation, and energy metabolism. Orthology-based comparative genomics identified six conserved orthogroups shared across at least two species, representing key stress-adaptive nodes including faFy acid synthesis initiation, metabolic stress buffering, transcription termination (Rho), ATP synthesis, peptidoglycan remodeling, and UDP-glucose–mediated envelope biosynthesis. Drug–target interaction analyses suggested that these conserved proteins are modulated by enzymatic inhibitors, metabolite analogs, or active-site competitors. Structural and docking analyses focused on a selected protein, FabF (β-ketoacyl-ACP synthase II), confirmed catalytically coherent binding of cerulenin within the active site, with high concordance between experimentally resolved and AlphaFold-predicted structures, supporting the reliability of structure-based prioritization. Conclusions: Overall, the results demonstrate that bacterial stress responses converge on evolutionarily conserved metabolic and regulatory elements essential for homeostasis and tolerance to perturbations, being the first work integrating core perturbomes data from different microorganisms. The proposed perturbome-informed framework provides a rational strategy to identify robust, broad-spectrum antimicrobial targets and highlights opportunities for drug repurposing and future experimental validation.